Clinical and sonographic improvement of developmental dysplasia of the hip: analysis of 948 patients - Bakti Karim; Lankinen Vilma; Helminen Mika; Välipakka Jarmo; Laivuori Hannele; Hyvärinen Anna (BMC, 2025)
Background: Developmental dysplasia of the hip is a common condition, which varies in severity. Abduction treatment is widely used to correct the development of the hips, but mild forms of DDH can also recover spontaneously. The purpose of this study was to evaluate factors affecting the rate of improvement of developmental dysplasia of the hip, and evaluate any risk factors slowing the process.
Material and methods: The study population consisted of patients diagnosed with DDH in Tampere University hospital in the years 1998-2018. Data were retrospectively collected, and associations between clinical variables and rate of improvement were analyzed. Alpha angles were assessed monthly, and associations between risk factors and improvement of alpha angles were studied. A total of 948 patients were included in the analysis.
Results: More severe first status of the hips was associated with faster improvement in dynamic ultrasound compared to milder DDH in univariate design in first 3 months of age; in the multivariable design, Ortolani positivity was conversely associated with lower alpha angles in 1-month follow-up. Immediate abduction treatment was associated with faster recovery rate compared to delayed abduction or watchful waiting. Female sex and positive family history were associated with slower rate of improvement and lower alpha angles. In multivariable design, female sex, positive family history and treatment strategy remained statistically significant as initiation time of the treatment explained the first found association of clinical hip status and the recovery rate after 2 months of age.
Conclusion: Female sex and positive family history might be independent risk factors for slower recovery in DDH before 6 months of age. These children might need special attention in their follow-up plans and abduction treatment.